NETWORK META-ANALYSIS: STRATEGIES TO IMPROVE INTERPRETATION - Phillips, Mark R (My University, 2022)
Network meta-analysis (NMA) is a relatively new methodology that allows for the comparison of multiple interventions, with particular benefit in allowing for the indirect comparison of interventions that have never been compared directly within randomized trials. There lacks a consensus with regard to many NMA methodology considerations, often leading to inadequately conducted NMAs. This provides an opportunity for novel research initiatives to develop and promote improved NMA methodologies; which will translate to improved information provided to clinicians for evidence-based decision making. This thesis highlights the need for better standards in NMA methodology and reporting, developed and user-tested a novel tool for effectively presenting NMA results to clinicians and key stakeholders, and utilized this tool within an NMA of surgical treatment options for displaced femoral neck fractures – an area of great interest for orthopaedic clinicians and researchers due to the numerous available treatment options and considerable equipoise that exists in this area. The NMA methods landscape will continue to evolve, and the components of this thesis provide the groundwork to solidify and advance the implementation of NMA results into clinical practice.